UNMET NEEDS FOR PERSONAL ASSISTANCE AMONG COMMUNITY-DWELLING U.S. CHINESE OLDER ADULTS - Kong, D (Innov Aging, 2018)
This poster will present findings on the prevalence and significant correlates of unmet needs for personal assistance among community-dwelling U.S. Chinese older adults, which have been poorly understood despite the rapid growth of this population. Cross-sectional data were obtained from the Population Study of Chinese Elderly in Chicago collected between 2011 and 2013 (N=3,157). Unmet needs were operationalized as having self-reported limitations in modified Katz Index of Independence in Activities of Daily Living (ADL; 8 items) and/or Lawton Instrumental Activities of Daily Living (IADL; 12 items) but assistance was not available all the time. Predictor variables included self-reported sociodemographic and health-related characteristics. Multivariable logistic regression analyses were conducted to examine significant correlates of unmet needs. Of 3,157 participants, 546 (17.3%) had any unmet needs (5.8% had 1, 3.5% had 2, and 8% had 3 or more unmet needs). Factors associated with a higher likelihood of unmet needs included older age (odds ratio [OR]=1.04, 95% confidence interval [CI]=1.02–1.05), higher income (OR=1.15, 95% CI=1.02–1.30), not married status (OR=1.40, 95% CI=1.06–1.84), lower acculturation level (OR=0.95, 95% CI=0.92–0.98), more chronic conditions (OR=1.18, 95% CI=1.10–1.27), poorer cognitive function (OR=0.48, 95% CI=0.40–0.56), higher levels of depressive symptoms (OR=1.10, 95% CI=1.07–1.13), lower levels of social support (OR=0.83, 95% CI=0.80–0.86), and higher levels of filial piety (OR=1.02, 95% CI=1.00–1.03). Implications of these findings in the development of community-based services and targeted intervention strategies to address unmet needs for personal assistance among diverse aging populations will be discussed.